2015
DOI: 10.1186/s12905-015-0175-4
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and abortion among young women in Rupandehi, Nepal

Abstract: BackgroundDespite liberalization of the Nepal abortion law, young women continue to experience barriers to safe abortion services. We hypothesize that marital status may differentially impact such barriers, given the societal context of Nepal.MethodsWe evaluated differences in reproductive knowledge and attitudes by marital status with a probability-based, cross-sectional survey of young women in Rupandehi district, Nepal. Participants (N = 600) were surveyed in 2012 on demographics, romantic experiences, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 22 publications
3
16
3
Order By: Relevance
“…In a patriarchal society like Nepal, married women are under intense pressure to have a male child that could contribute to abortion [ 40 ]. The pressure on women to bear sons as well as knowing those seeking abortion for gender preferences is a difficult task for health workers [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a patriarchal society like Nepal, married women are under intense pressure to have a male child that could contribute to abortion [ 40 ]. The pressure on women to bear sons as well as knowing those seeking abortion for gender preferences is a difficult task for health workers [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, women who are cohabiting may not want to give birth outside marriage to escape ridicule from society. Moreover, unmarried women are more likely to indicate that they will support a friend who needed an abortion or feel confident that they could help a friend obtain the service [ 54 ]. The high prevalence of pregnancy termination among cohabiting women can also be linked to the high prevalence of unintended pregnancies among never married women [ 23 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…History of abortion was given by 3.2% respondents in a study by Anderson et al 22 while our study had a 14% respondents with history of abortion. The increase in our respondents may be due to the fact of inclusion of women of reproductive age group 16-49 years, as in earlier study the sample included women of 16-24 years only.…”
Section: Discussionmentioning
confidence: 59%
“…However, a contradictory finding has been reported in study in Rupandehi District. 22 More than half (65%) of respondents had a knowledge about abortion law with 81.40% knowing that abortion was legal in our country. In addition, a study done at Kathmandu Marie Stopes clinic 23 showed that among the abortion seekers 59% knew that abortion was legal and two most conditions for abortion was mentioned as health status of mother (43.4%) and incase of rape/incest (32.2%).…”
Section: Discussionmentioning
confidence: 91%